2008
DOI: 10.4103/0974-2700.41785
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the utility of ultrasound in Liberia

Abstract: Sub-Saharan Africa has sparse imaging capacity, and data on ultrasound (US) use is limited. We collected prospective data on consecutive patients undergoing US to assess disease spectrum and US utility in Liberia. A total of 102 patients were prospectively enrolled. Average age was 33 years (0-84), 80% were female. US indications were: 53% Obstetrics/Gynecology (OB/GYN) (24% gynecologic, 17% second/third trimester, 12% first trimester), 14% hepatobiliary, 10% intraperitoneal/intrathoracic fluid, 8% cardiac, 5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 11 publications
3
58
0
Order By: Relevance
“…(Table 1) Four articles documented the use of ultrasound by medical volunteers on missions in Ghana, Liberia, Mexico and Gambia (Kobal et al. 2004a,b; Kotlyar & Moore 2008; Spencer & Adler 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Table 1) Four articles documented the use of ultrasound by medical volunteers on missions in Ghana, Liberia, Mexico and Gambia (Kobal et al. 2004a,b; Kotlyar & Moore 2008; Spencer & Adler 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Of the expert opinion articles, 4 (33%) were from sub-Saharan Africa and 9 (75%) from high-income countries. (Table 1) Four articles documented the use of ultrasound by medical volunteers on missions in Ghana, Liberia, Mexico and Gambia (Kobal et al 2004a,b;Kotlyar & Moore 2008;Spencer & Adler 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greatest impact on patient management was seen with first trimester obstetric ultrasound, followed by FAST, cardiac and second/third trimester ultrasound exams; the smallest impact was seen in RUQ and gynecologic studies [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The needs in low‐ and middle‐income countries are varied, however. A prior investigation in Liberia demonstrated that bedside ultrasound may have the most impact in obstetric care 5 . A South African study in 2013 found that point‐of‐care ultrasound was widely used in the emergent clinical setting and that the ultrasound modalities most commonly used did reflect the local burden of disease.…”
mentioning
confidence: 99%